Isolation, Characterization, Anti-Hyperglycemic Activity And Molecular Docking Studies Of Constituents Isolated From Endiandra Kingiana And Beilschmiedia Lumutensis (Lauraceae) - Saad, Nur Amirah (2022)
A preliminary study upon the bark of Endiandra kingiana (E. kingiana) and Beilschmiedia lumutensis (B. lumutensis) revealed promising anti-hyperglycemic agents against α-amylase and α-glucosidase inhibition activity, which prompted its chemical investigation.